Physical Profiling of Taekwondo Athletes at the Cirebon District Training Center - Zahwa Siska Putri Permana; Yati Ruhayati; Iman Imanudin imanudin (Universitas Negeri Semarang, 2026)
Physical condition is the main foundation that determines the quality of athletes' performance in taekwondo. The characteristics of the competition, which require explosive movements, high speed, and the ability to maintain intensity, make aerobic endurance, speed, and muscle strength crucial physical components. This study aims to determine and describe the physical condition profile of taekwondo athletes from the Cirebon District Training Center. The research method used is quantitative descriptive with a cross-sectional approach. The research sample consisted of 11 athletes (5 females and 6 males) aged 15–20 years who were selected using total sampling technique. Data were obtained from physical condition tests, including a 20-meter sprint, 200-meter sprint, 1-minute sit-ups, 1-minute push-ups, 1-minute back-ups, and the Balke Test to estimate VO₂Max. Data analysis was performed using descriptive statistics in the form of mean values, standard deviations, minimum values, and maximum values. The results showed that, in general, the athletes' physical condition was in the adequate category. However, when assessed based on the norms, most athletes were still in the poor to very poor category. There were clear variations in ability among athletes in each component of physical condition. These findings indicate a gap between the actual physical condition of athletes and the performance standards required in taekwondo. Therefore, a more focused, structured, and sustainable physical training program is needed so that improvements in athletes' physical condition can be more evenly distributed and optimal.